2018
DOI: 10.1371/journal.pone.0193992
|View full text |Cite
|
Sign up to set email alerts
|

Higher parental occupational social contact is associated with a reduced risk of incident pediatric type 1 diabetes: Mediation through molecular enteroviral indices

Abstract: We aimed to examine the association between parental occupational social contact and hygiene factors on type 1 diabetes (T1D) risk and possible mediation of these effects through child enteroviral infection. We interviewed 333 incident T1D cases and 660 controls from 2008–2011 in Melbourne, Australia. Enteroviral indices (ribonucleic acid by reverse transcription polymerase chain reaction and Coxsackie B virus antibody levels) in peripheral blood were measured in nested case control samples. Parent occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The relationship between islet autoantibodies and CVB serotypes has also been observed in other cohorts collected in European countries [78] and subsequently in prospective studies carried out in Europe, North America, and Australia [79,80]. Recently, the large international TEDDY birth cohort study reported an association between detection of species B EVs (particularly CVBs) in stool samples by Illumina mass sequencing and subsequent initiation of islet autoimmunity (data presented in the Immunology of Diabetes Society meeting in London, October 2018).…”
Section: Identification Of Diabetogenic Ev Typessupporting
confidence: 62%
“…The relationship between islet autoantibodies and CVB serotypes has also been observed in other cohorts collected in European countries [78] and subsequently in prospective studies carried out in Europe, North America, and Australia [79,80]. Recently, the large international TEDDY birth cohort study reported an association between detection of species B EVs (particularly CVBs) in stool samples by Illumina mass sequencing and subsequent initiation of islet autoimmunity (data presented in the Immunology of Diabetes Society meeting in London, October 2018).…”
Section: Identification Of Diabetogenic Ev Typessupporting
confidence: 62%
“…Maternal occupational social contact: levels Low, Medium, and High as outlined in 21 . Paternal occupational social contact: levels Low, Medium, and High as outlined in 21 . Disinfectant use in T1/2/3: values = none, <1 week, about 1 week, a few times per week, every day.…”
Section: Resultsmentioning
confidence: 99%
“…Any formal childcare in first 12 months: baby received any regularly scheduled formal childcare in a childcare center in the first 12 months, no otherwise. Maternal/Paternal occupational social contact: low or not elsewhere classified, medium 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations